Environmental sustainability strategy and its role in developing the strategic performance of government enterprises in Al Kharj Governorate - Ibrahim, Khaled Ahmed AbdelAl (Research Journal in Advanced Humanities, 2024)
The external environment’s rapid and intense competition has compelled organizations to adapt to these changes, comply with their requirements, and mitigate their negative impacts. In order to ensure their survival and continuity, organizations must respond to their surroundings in consideration of their social responsibility by implementing systems and strategies that safeguard the natural and social environment. Therefore, the present study aims to focus on the implications of environmental sustainability, management, and efficiency for the operations of businesses. Among the aspects that can be impacted by these topics is the strategic performance of businesses, which is contingent on their commitment to the requirements of strategic performance. In addition, the present study is interested in placing emphasis on various internal and external factors, such as cultivating and enhancing organizational capabilities and resources, striving to attain customer contentment, and bolstering their allegiance or dedication to social responsibility.  As a result, the present study examined two significant subjects for organizations: strategic performance and the strategy of environmental sustainability. Specifically, it investigated the impact of such strategies on enhancing the strategic performance of government facilities in Al-Kharj Governorate. This was confirmed through an examination of relevant literature and analysis.